2016
DOI: 10.1021/acs.accounts.6b00080
|View full text |Cite
|
Sign up to set email alerts
|

N,N′-Diamidocarbenes: Isolable Divalent Carbons with Bona Fide Carbene Reactivity

Abstract: Since the first reported isolation of a carbene just over a quarter century ago, the study of such compounds-including stable derivatives-has flourished. Indeed, N-heterocyclic carbenes (NHCs), of which imidazolylidenes and their derivatives are the most pervasive subclass, feature prominently in organocatalysis, as ligands for transition metal catalysts, and as stabilizers of reactive species. However, imidazolylidenes (and many other NHCs) typically lack the reactivity characteristic of electrophilic carbene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(56 citation statements)
references
References 82 publications
0
56
0
Order By: Relevance
“…Recently, Bertrand and co‐workers reported the successful activation of N−H bonds of ammonia by ambiphilic CAAC under mild conditions . In addition, highly electrophilic diamido carbene (DAC) can activate ammonia ,. It was found that the primary approach for splitting of NH 3 by DAC is the interaction of amino lone pair with the vacant 2p orbital at the carbenic carbon whereas in case of CAAC the key step involves interaction of carbenic lone pair with one of the σ* N−H orbital of NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bertrand and co‐workers reported the successful activation of N−H bonds of ammonia by ambiphilic CAAC under mild conditions . In addition, highly electrophilic diamido carbene (DAC) can activate ammonia ,. It was found that the primary approach for splitting of NH 3 by DAC is the interaction of amino lone pair with the vacant 2p orbital at the carbenic carbon whereas in case of CAAC the key step involves interaction of carbenic lone pair with one of the σ* N−H orbital of NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[1, 3b] This agrees well with calculations on (H,C,P) 3 isomers,w hich predict that the cyclic triphosphabenzenes are more than 30 kcal mol À1 lower in energy than prismane cages. [4] Singlet N-heterocyclic carbenes (NHCs) [5] and cyclic diamidocarbenes (DACs) [6] may stabilize otherwise reactive molecules,a nd recently cyclic and acyclicC 2 P 2 skeletons as possible forms of "dicarbondiphosphide" could be isolated with these as substituents. [7] Herein we report the synthesis of neutral tricarbontriphosphide radicals (L 3 C 3 P 3 )C and their oxidation to the corresponding cations (L 3 C 3 P 3 )…”
mentioning
confidence: 99%
“…[1, 3b] This agrees well with calculations on (H,C,P) 3 isomers,w hich predict that the cyclic triphosphabenzenes are more than 30 kcal mol À1 lower in energy than prismane cages. [4] Singlet N-heterocyclic carbenes (NHCs) [5] and cyclic diamidocarbenes (DACs) [6] may stabilize otherwise reactive molecules,a nd recently cyclic and acyclicC 2 P 2 skeletons as possible forms of "dicarbondiphosphide" could be isolated with these as substituents. [7] Herein we report the synthesis of neutral tricarbontriphosphide radicals (L 3 C 3 P 3 )C and their oxidation to the corresponding cations (L 3 C 3 P 3 ) + (L = CAAC).…”
mentioning
confidence: 99%
“…[14] Ellipsoids are set to 50 %p robability;Hatoms, solvent molecules, anion, and substituents on CAAC for 5b and 7b are omitted for clarity. Selected distances []and angles [8 8]: a) 2b:P1-P2 2.2360 (6), P1-C1 1.623(2), C1-C2 1.324(3);P 2-P1-C1 99.79 (8), P1-C1-C2 173.18(16);b) 5b:P1-P2 2.6846 (6), P1-P3 2.2082 (6), P1-C1 1.8494(18),C 1-P2 1.8577(18), P2-C3 1.8578(18), C3-P1 1.8412(18),P 2-C5 1.8828(18), P3-C5 1.8040(18), C1-C2 1.357(2), C3-C4 1.352(2), C5-C6 1.386(2); C5-P3-P1 94.40 (6), P3-P1-C3 94.15 (6), P3-P1-C1 91.61 (6);c )6e:P 1-P1' 2.2508 (8), P1-C1 1.6336(17),C 1-C2 1.324(2);P 1 '-P1-C1 99.30 (7), P1-C1-C2 175.67 (14);d)7b:P 1-P2 2.755, P1-P3 2.2252 (7), P1-C1 1.939(2), C1-P2 1.941(2), P2-C3 1.837(2), C3-P1 1.910(2), P2-C5 1.856(2), P3-C1 1.808(2), P3-C5 1.821(2), C1-C2 1.443(3), C3-C4 1.365(3), C5-C6 1.371(3);C 5-P3-P1 84.05 (9), C5-P3-C1 84.05 (9), P3-P1-C3 99.22 (7), P3-P1-C1 54.09 (6).…”
mentioning
confidence: 99%